Pencarian Rute Indoor Terpendek dalam Lingkungan Universitas Kristen Petra Surabaya menggunakan Algoritma D* Lite berbasis Android - Richard Hans Krisnajana; Agustinus Noertjahyana (Jurnal Infra, 2022)
In today's era, a large building divided into several floors often confuses visitors in looking for a place / room and spends a lot of time in vain, one example is the Petra Christian University Surabaya environment. The application that will be made can make it easier for students, lecturers, staff and visitors to Petra Christian University Surabaya in finding the shortest route to their destination. To run the application, a server is needed in the form of a database to store nodes, space data, wi-fi data, and geomagnetic data. Data retrieval is done manually and processed so that it can be used as a reference. After the data retrieval process, the user can enter input in the form of their destination and the system will calculate the shortest route and display the route to the user. Based on the results of the tests that have been carried out, the application that has been made is able to provide the shortest route and display it to the user. In addition, the application is also able to provide the shortest route calculation with a short average time, and provide the user with an estimate of the exact location and time during the navigation process